Faster time to automated elevation of the head and thorax during cardiopulmonary resuscitation increases the probability of return of spontaneous circulation. (January 2022) - Moore, Johanna C.; Duval, Sue; Lick, Charles; Holley, Joseph; Scheppke, Kenneth A.; Salverda, Bayert; Rojas-Salvador, Carolina; Jacobs, Michael; Nystrom, Paul; Quinn, Ryan; Adams, Paul J.; Debaty, Guillaume P.; et al.
Abstract: Objectives: Resuscitation in the Head Up position improves outcomes in animals treated with active compression decompression cardiopulmonary resuscitation and an impedance threshold device (ACD + ITD CPR). We assessed impact of time to deployment of an automated Head Up position (AHUP) based bundle of care after out-of-hospital cardiac arrest on return of spontaneous circulation (ROSC). Methods: Observational data were analyzed from a patient registry. Patients received treatment with 1) ACD + and/or automated CPR 2) an ITD and 3) an AHUP device. Probability of ROSC (ROSCprob) from the 9-1-1 call to AHUP device placement was assessed with a restricted cubic spline model and linear regression. Results: Of 11 sites, 6 recorded the interval from 9-1-1 to AHUP device (n = 227). ROSCprob for all rhythms was 34%(77/227). Median age (range) was 66 years (19-101) and 68% men. The ROSCprob for shockable rhythms was 47%(18/38). Minutes from 9-1-1 to AHUP device (median, range) varied between sites: 1) 6.4(4, 15), 2) 8.0(5, 19), 3) 9.9(4, 12), 4) 14.1(6, 36), 5) 15.9(6, 34), 6) 19.0(8, 38), (p = 0.0001). ROSCprob also varied; 1) 55.1%(16/29), 2) 60%(3/5), 3) 50%(3/6), 4) 22.7%(17/75), 5) 26.4%(9/34), and 6) 37.1%(29/78), (p = 0.019). For all rhythms between 4 and 12 min (n = 85),  ROSCprob declined 5.6% for every minute elapsed (p = 0.024). For shockable rhythms, between 6 and 15 min (n = 23),  ROSCprob declined 9.0% for every minute elapsed (p = 0.006). Conclusions: Faster time to deployment of an AHUP based bundle of care is associated with higher incidence of ROSC. This must be considered when evaluating and implementing this bundle.